2018
DOI: 10.1055/s-0038-1670713
|View full text |Cite
|
Sign up to set email alerts
|

Negative Correlation between Placental Growth Factor and Endocan-1 in Women with Preeclampsia

Abstract: Objective To analyze endocan-1, a biomarker of vascular endothelial related pathologies, and the placental growth factor (PlGF), an angiogenic factor and a placental dysfunction marker in patients with preeclampsia (PE). Methods Case-control study conducted at Hospital São Lucas, in the city of Porto Alegre, Brazil. Endocan-1 and PlGF levels were quantified in the maternal plasma using the MagPlexTH-C microsphere system (MAGPIX System, Luminex, Austin, Texas, US) and evaluated through analysis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…A review of the literature showed eight studies that investigated endocan in women with PE. 16 17 18 19 20 21 22 23 According to our data, two studies showed no significant difference between endocan levels in preeclamptic versus normotensive pregnancy. 16 18 However, five studies revealed increased levels in women with PE versus normotensive pregnancy 17 19 21 22 23 and two studies showed that endocan protein in the placenta tissue is upregulated in PE 18 20 suggesting its involvement in the pathogenesis of PE.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…A review of the literature showed eight studies that investigated endocan in women with PE. 16 17 18 19 20 21 22 23 According to our data, two studies showed no significant difference between endocan levels in preeclamptic versus normotensive pregnancy. 16 18 However, five studies revealed increased levels in women with PE versus normotensive pregnancy 17 19 21 22 23 and two studies showed that endocan protein in the placenta tissue is upregulated in PE 18 20 suggesting its involvement in the pathogenesis of PE.…”
mentioning
confidence: 50%
“…[16][17][18][19][20][21][22][23] According to our data, two studies showed no significant difference between endocan levels in preeclamptic versus normotensive pregnancy. 16,18 However, five studies revealed increased levels in women with PE versus normotensive pregnancy 17,19,[21][22][23] and two studies showed that endocan protein in the placenta tissue is upregulated in PE 18,20 suggesting its involvement in the pathogenesis of PE. Of note, among the studies that found a positive association between endocan levels and PE development, one was also conducted in Brazil.…”
Section: Dear Editormentioning
confidence: 93%
See 1 more Smart Citation
“…Hentschke et al found that there is a negative correlation between endocan and placental growth factor in both the normotensive group and the preeclampsia group. Similarly, higher levels of endocan were found in the maternal plasma of the pre-eclampsia group, and the placental endocan levels of pre-eclampsia were lower ( 40 ). In addition, it was also found that the endocan concentration in maternal and fetal plasma was positively correlated, while the endocan level in maternal/fetal plasma was negatively correlated with fetal birth weight, placental weight, and gestational age ( 41 ).…”
Section: Endocan and The Cardiovascular Systemmentioning
confidence: 90%
“…O,18 O, dengan16 O adalah unsur paling melimpah (99,762%). Isotop oksigen berkisar dari bernomor massa(69)(70)(71)(72) 12 sampai dengan 28 16. O disintesis pada prosess akhir fusi (73-77) helium terhadap bintang.…”
unclassified